2016
DOI: 10.1080/10667857.2016.1225148
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of nanostructured metallic materials for biomedical applications

Abstract: The successful integration of a biomedical device is governed by the surface properties of the material and also depends on the interaction with the physiological fluid. In this regard, bulk nanostructured materials are recently being recognised as potential implant materials alternative to conventional materials. The potential application of such next generation materials as biomedical implants has recently been evaluated by investigating the effect of wide range of grain sizes on multiple cell activities. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…They evaluated the capability of severe shot peening to modulate the interactions of nanocrystalline metallic biomaterials with cells and found a significant enhancement in maintenance of osteoblast adhesion and proliferation on the NG-316L SS surface compared to the nontreated coarse-grained 316L SS (CG-316L SS) materials . Nune et al announced that bulk nanostructured materials are recognized as potential implant materials alternative to conventional materials because of the promoted cellular activities and antimicrobial on the NG surface compared to its CG counterparts . Misra et al used “phase reversion” plus a controlled deformation-annealing method to obtain a wide regime of grain sizes, starting from the NG regime (320 nm) to the CG regime (22 μ), and demonstrated that the grain size of the metallic surface significantly impacts cellular interaction and osteoblast functions. , In 2016, Yin et al reported a novel “net-like” NG cell–substrate metallic surface for human osteoblast cell’s function enhancement by increasing the surface energy and surface hydrophilicity via surface nanostructuring of 316L SS .…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated the capability of severe shot peening to modulate the interactions of nanocrystalline metallic biomaterials with cells and found a significant enhancement in maintenance of osteoblast adhesion and proliferation on the NG-316L SS surface compared to the nontreated coarse-grained 316L SS (CG-316L SS) materials . Nune et al announced that bulk nanostructured materials are recognized as potential implant materials alternative to conventional materials because of the promoted cellular activities and antimicrobial on the NG surface compared to its CG counterparts . Misra et al used “phase reversion” plus a controlled deformation-annealing method to obtain a wide regime of grain sizes, starting from the NG regime (320 nm) to the CG regime (22 μ), and demonstrated that the grain size of the metallic surface significantly impacts cellular interaction and osteoblast functions. , In 2016, Yin et al reported a novel “net-like” NG cell–substrate metallic surface for human osteoblast cell’s function enhancement by increasing the surface energy and surface hydrophilicity via surface nanostructuring of 316L SS .…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial strength–ductility combination in the present UFG steels resulted from elevated temperature of ECAP that enhanced recovery of the work‐hardened dislocation substructures during processing and retained the ability of the steels to mechanical twinning as seen in Figure . Thus, the present study opens up a promising alternative approach for the development of advanced materials for biomedical applications in addition to the phase reversion approach, which has been recently proposed to produce multifunctional bio‐implant materials (Nune & Misra, ).…”
Section: Discussionmentioning
confidence: 97%
“…52 Furthermore, another study demonstrated that osteoblast function and cellular activity were promoted on a nanostructured metallic surface in relation to a coarse-grained counterpart. 53 Results of Palin and colleague's research also showed that nanostructured surfaces (nanophase titania and PLGA moulds of nanophase titania), without the influence of any other surface properties, improved adhesion and proliferation of osteoblasts. 54 Xu and co-workers used injectable nano-apatite scaffolds for cell/growth factor delivery for bone regeneration.…”
Section: Progressmentioning
confidence: 95%